Rekonstruksi Adab Guru dan Murid Menurut Ibn Jamā‘ah dalam Tadzkirotus Sāmi’ dan Relevansinya terhadap Pendidikan Modern - Al Azhari, Yahya Husein; Mutalib, Wahyudi; Rusminingsih, Eka Sri; Hidayah, Samsiyah Nuril; Khoiriyah (JDP (JURNAL DINAMIKA PENDIDIKAN), 2026)
The ethical crisis in teacher–student relationships within modern education, particularly in the digital era, is characterised by the erosion of exemplary conduct, the decline of respect, and the growing dominance of mechanistic and transactional pedagogical interactions. This phenomenon underscores the urgency of re-establishing an ethical foundation for education rooted in the Islamic intellectual tradition. This study aims to reconstruct the concept of adab (ethical conduct) of teachers and students according to Ibn Jamā‘ah in Tadzkirotus Sāmi‘ wa al-Mutakallim fī Adab al-‘Ālim wa al-Muta‘allim and to analyse its relevance within the context of contemporary education. This research employs a qualitative approach, utilising a library-based method, and applies thematic analysis to primary texts and relevant secondary sources. The findings indicate that, according to Ibn Jamā‘ah, the adab of teachers is founded upon four principal elements: moral exemplarity, scholarly integrity, pedagogical wisdom, and spiritual–moral relationality. Meanwhile, the adab of students encompasses five essential principles: respect, diligence in learning, discipline, proper questioning etiquette, and self-purification. The conceptual reconstruction of these values demonstrates that Ibn Jamā‘ah’s thought is not merely normative and historical in nature but possesses significant adaptive capacity for contextualisation within modern educational systems, including digital and blended learning environments. This study affirms that adab constitutes the epistemological and ethical foundation of education; thus, its revitalisation is a prerequisite for the realisation of an educational model oriented not only towards cognitive achievement but also towards character formation and moral maturity.